2012
DOI: 10.2215/cjn.04040411
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Therapy in Chronic Kidney Disease and End Stage Renal Disease

Abstract: SummaryVitamin D has garnered much research and debate about supplementation in recent years, not only as it pertains to patients with kidney disease but also to those in the general population. This review discusses observational and available clinical trial evidence about the effects of both calcitriol and vitamin D analogs (active) and ergocalciferol and cholecalciferol (nutritional) vitamin D in patients with CKD and ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 68 publications
6
76
0
3
Order By: Relevance
“…Low level of vitamin D3 is associated with osteoporosis, rickets, cardiovascular disorder, some autoimmune disease, multiple sclerosis, diabetes mellitus and some cancers (9). It has been suggested that low level of vitamin D decreases the survival of general population and CKD and HD patients (10,11). Recent observations showed a positive relation between level of 25(OH)D and 1.25(OH)2 D in CKD patients (8,12,13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low level of vitamin D3 is associated with osteoporosis, rickets, cardiovascular disorder, some autoimmune disease, multiple sclerosis, diabetes mellitus and some cancers (9). It has been suggested that low level of vitamin D decreases the survival of general population and CKD and HD patients (10,11). Recent observations showed a positive relation between level of 25(OH)D and 1.25(OH)2 D in CKD patients (8,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Then at the base line we evaluated the relations between the serum level of vitamin D3 with blood level of PTH, Ca, P, ALP and CA × P product; then effect of administration of vitamin D3 on these biochemical markers was investigated. Melamed and Thadhani reported that there is an association between stage of CKD and vitamin D deficiency (11). This association is probably related to poor appetite, protein restriction, activity loss and less exposure to sunlight (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Treatment with vitamin D in patients with CKD improves their long-term survival and reduces their cardiovascular risk. 10,11 T h e c i r c u l a t i n g l e v e l o f 25-hydroxy-vitamin D (25(OH)D) is the best marker of a subject's status in terms of vitamin D levels based on its prolonged circulation half-life and the fact that it does not build up in tissues. The measurement of 25(OH)D reflects vitamin D dietary intake, vitamin D produced in the skin from exposure to sunlight, and vitamin D made in the liver from adipose tissue deposits.…”
Section: Introductionmentioning
confidence: 99%
“…3 H o w e v e r , l e v e l s m a y v a r y depending on the season, duration of exposure to sunlight, sunscreen use, dietary intake, and urinary loss of vitamin D binding protein. 10,11 Studies have been conducted worldwide to establish vitamin D deficiency prevalence among children 16 The objectives of this study included establishing the prevalence of vitamin D deficiency among children with CKD and identifying associated risk factors and the relationship with parathormone (PTH) intact molecule.…”
Section: Introductionmentioning
confidence: 99%